SOBRE UN PYGIDIIDAE (PISCES, SILURIFORMES) DEL EOCENO DE RIO NEGRO (Ameghiniana, 2013)
A new genus and species of Pugicliiclae, found in Las Bayas, Rio Negro Province, Argentfi'la, is described. Las Bayas is a component of the 'Serie Andesitica', called Cautivalitimse by Suero, of Eocene age; it is correlated with the tertiary tuffs of El Mirador (Chubut). By its opercule and interopercule thorny this specimen is a Pygicliidae, but it differs from all known living genera by the presence of three very developed rays, not divided·, and by the thorny aspect in the dorsal fin. On the other hand, some similarities with the Pime- locliclae indicate that this new genus is likely to be near the ancestral. stock 6£ both families, and that their differentiation took. place probably during pretertiary times.